The Children's War - Kennedy, R. author. aut Link
X, 189 p.
Keywords: British children were mobilised for total war in 1914-18. It dominated their school experience and they enjoyed it as a source of entertainment. Their support was believed to be vital for Britain's present and future but their participation was motivated by a desire to remain connected to their absent fathers and brothers.